1999
DOI: 10.1191/096120399678840927
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil for the treatment of systemic lupus erythematosus: an open pilot trial

Abstract: Mycophenolate mofetil is a promising option in immunosuppressive treatment of patients with moderate and severe systemic lupus erythematosus who did not show a satisfactory response to other immunosuppressives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 21 publications
1
64
0
2
Order By: Relevance
“…However, most of the studies reported to date have been either anecdotal (21,29) or based on uncontrolled observations of adult (16,27,39) and pediatric (9) SLE patients. In a cohort of 42 patients with diffuse proliferative lupus nephritis, Chan and co-workers (10) compared the renal protective effect and the toxicity of a combined prednisolone and MMF treatment given for 12 mo (group 1; 21 patients) with those of an association of prednisolone and cyclophosphamide maintained for 6 mo, followed by treatment with prednisolone and azathioprine for another 6 mo (group 2; 21 patients).…”
Section: Beneficial Effects Of Mmf In Immunemediated Nephropathiesmentioning
confidence: 99%
“…However, most of the studies reported to date have been either anecdotal (21,29) or based on uncontrolled observations of adult (16,27,39) and pediatric (9) SLE patients. In a cohort of 42 patients with diffuse proliferative lupus nephritis, Chan and co-workers (10) compared the renal protective effect and the toxicity of a combined prednisolone and MMF treatment given for 12 mo (group 1; 21 patients) with those of an association of prednisolone and cyclophosphamide maintained for 6 mo, followed by treatment with prednisolone and azathioprine for another 6 mo (group 2; 21 patients).…”
Section: Beneficial Effects Of Mmf In Immunemediated Nephropathiesmentioning
confidence: 99%
“…In an established autoimmune disease such as MG, treatment with a drug that is not cytocidal would not be expected to produce rapid benefit. [6][7][8] Because preexisting autosensitized lymphocytes are not eliminated by MM, improvement depends upon these lymphocytes dying, which occurs gradually. 4 Immunomodulatory treatment for MG entails evaluating several factors, including onset of action of the available agents, their efficacy, and their side effects.…”
mentioning
confidence: 99%
“…5 It has also been reported to be of benefit in other immune-mediated diseases such as rheumatoid arthritis, Crohn's disease, and systemic lupus erythematosus. [6][7][8] The principal adverse reactions associated with MM include diarrhea, leukopenia, sepsis, vomiting, and a higher frequency of certain types of infections. It is thought to entail a lower risk for late malignancies than other drugs such as azathioprine and cyclophosphamide, which can be mutagenic or can decrease T-cell surveillance over lymphomas related to EpsteinBarr virus.…”
mentioning
confidence: 99%
“…While ethnicity plays a role in the response to immunosuppressive treatment in LN [34], it seems that the response to MF in refractory or relapsing disease does not differ in patients from different ethnic groups. In fact, the cases reported to date are from the USA [8,18,19], South America [13,26], Canada (in children) [35], Europe [9,10,12,14,20,23,24,25,30], Australia [21], and Asia [11,22,27,28,29]. …”
Section: Discussionmentioning
confidence: 99%
“…The first clinical series of patients with relapsing or refractory LN after treatment with CYC who received MF were published in the late 1990s and revealed an improvement in proteinuria and renal function [8,18,19,20]. Subsequently, several observational and uncontrolled studies also described the beneficial effect of MF in refractory or relapsing LN, indicating that switching from CYC to MF is a reasonable alternative strategy [9,10,11,12,13,14,21,22,23,24,25,26,27,28,29].…”
Section: Discussionmentioning
confidence: 99%